Widening gap of educational opportunity? A longitudinal study of educational inequality in China - Min-Dong Paul Lee (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
This study attempts to convey an accurate and dynamic account of educational inequality in China during the last decade. The study finds that there is clear evidence of rapid expansion of education, and younger students all over China are benefiting from the expansion. One of the most notable achievements is the virtual elimination of gender bias against girls in educational attainment. However, analysis of province-level school enrolment data over the last decade shows evidence of persistent regional inequality of educational attainment. Students from inland provinces continue to face strong structural inequality in educational opportunity, and this structural inequality becomes more pronounced as they progress to higher grades. Moreover, inter-cohort analysis reveals that the inter-provincial inequality in upper grades is increasing for younger cohort of students, meaning that educational inequality in China is deteriorating further. Lastly, a decomposition analysis shows that the causes of inter-provincial educational inequality are quite complex and cannot simply be explained by the urban-bias hypothesis that is often suggested as the main source of income inequality. – China ; inequality ; education ; regional disparity ; educational inequality
Keywords: H52; I20; J24; J62; O15; P36; 330; Bildungsniveau; Regionale Disparität; China